Carta de Bento XIV a D. João V, agradecendo-lhe o que fizera para a passagem do Arcebispo de Goa para a Índia. (1746)
This document is a copy of a letter dated 14 February 1746, originating from Rome and addressed to King João V of Portugal and the Algarves. The original correspondence, dated 16 January in the sixth year of the pontificate of an unnamed Pope, conveys formal ecclesiastical gratitude for the acquisition made by His Majesty (S. M.) benefiting the clergy. The Pope expresses appreciation for the monarch’s support of the Church, acknowledging his pious conduct and reaffirming ongoing spiritual intercessions on behalf of the Portuguese crown. Emphasising the Pope’s apostolic blessing bestowed upon King João V and his entire royal family, the letter underscores the close relationship between the Holy See and the Portuguese monarchy during the mid-18th century. Written in Latin with a postscript notation in Portuguese indicating the date and recipient, the document serves as a diplomatic and religious communication reflecting the ceremonial and devotional practices of the period. It highlights the role of the Catholic Church in affirming monarchical authority through spiritual endorsement and reveals the mechanisms of reciprocal recognition between secular rulers and papal authority in early modern Europe. This transcription provides scholars with primary source material pertinent to the study of Iberian- Vatican relations, religious patronage, and the intersection of monarchy and ecclesiastical power in the 18th century.
Document 11.
Keywords: Apostolic Blessing; Baroque Era; Catholic Church; Ceremonial Practices; Church-State Relations; Clergy Support; Diplomatic Communication; Ecclesiastical Diplomacy; Goa Archbishop; Historical Correspondence; Holy See; Indian Mission; King João V; Latin documents; Monarchical Authority; Papal Letter; Portuguese Monarchy; Postscript in Portuguese; Reciprocal Recognition; Relations Portugal Vatican; Religious Endorsement; Royal Patronage; Sixth Pontificate; Spiritual Intercessions; Transcription; Unnamed Pope